Presencia de un segundo conducto en la morfología de los incisivos inferiores. - Sarango Gonzalez, Tupac Augusto (2024)
The present research project entitled "Presence of a second canal in the morphology of lower incisors" focused on analyzing this anatomical variation by reviewing scientific articles. The main objective was to investigate the prevalence of this canal in the mentioned dental pieces, using available scientific literature as a basis. In this literature review, 43 articles from various databases, such as Scopus, PubMed, Scielo, and ProQuest, among others, were evaluated. The selected documents were those written in English, Spanish, and Portuguese, following the principles of the PICO methodology and using DeCS terms, as well as the boolean operators "AND" and "OR." This methodological approach facilitated the identification of relevant scientific articles for inquiry while allowing the exclusion of those that did not meet the predefined criteria, thus ensuring the quality and relevance of the resources consulted. As the main result of the research, it was determined that 25.5% of permanent lower lateral incisors exhibit the presence of two canals, one vestibular and one lingual. This anatomical variation is more frequently observed in male individuals. In conclusion, when performing endodontic treatment on mandibular incisors, it is essential to consider the prevalence percentage of the second canal in these dental pieces. For its localization, the preferred examination is Cone Beam Computed Tomography (CBCT) since it accurately assesses this anatomical variation by offering three-dimensional images, thus providing a more comprehensive field of view. However, periapical radiography with the Clark technique could be a viable alternative in specific situations. Additionally, it is essential to know about the possible complications associated with this anatomical variation as it directly influences treatment planning. This comprehensive approach, based on precise information and informed diagnoses, improves the effectiveness and success of endodontic procedures in mandibular incisors.